Understanding experiences of recruiting for, and participating in, genomics research and service transformation: the 100,000 Genomes Project, 2015-17 - Ryan, S; Rees, S; Holdsworth, E; Howard, J; Knight, F; Locock, L; Stepney, M; Martin, A; Mays, N (Policy Innovation and Evaluation Research Unit, 2020)
The 100,000 Genomes Project (the ‘Project’), announced in December 2012, was established to: • develop new capability and capacity in genomic medicine in order to transform the provision of health services in England; • create new capability for clinical genomics research and • establish an infrastructure for the protection and analysis of clinical and genomic data.